Proposed new design and image of fitness center for Exxonmobil at Level 6, Menara Exxonmobil, Kuala Lumpur City Center, 50088, Kuala Lumpur / Seri Munirah Mustaza - Mustaza, Seri Munirah (Faculty of Architecture, Planning and Surveying, 2008)
The report is mainly about upgrading the Fitness Center for Exxonmobil Recreation Center. The purposed of this project is to give a new design and image that shows the identity for Exxonmobil because the issues now, the fitness center does not show the image of a fitness center. This project also was built to give new and better facilities. To make this project more interesting, lounge area has been added to the fitness center as a relaxation area after workout. In running this project most important thing is to add more equipment in the center and have the right traffic flow in the fitness center. A few researches have been made in a few local fitness center and international such as True Fitness Subang Jaya, Fitness First and Pusat Gymnasium Rakyat. A few advantage and disadvantage also have been made and this will help to make the project also as guidance to the project. The fitness center was introduced to give the workers of Exxonmobil new facilities and to attract the workers to come and exercise and at the same time enjoy workout. The advantage of this fitness center, it is purposely for their workers and it easier for them to come. In conclusion, the new design fitness center that will be upgrade should have the identity of Exxonmobil besides from having the suitable concept.